Molecular and Parasitological Study on Selected Opportunistic Intestinal Parasites in Immunocompromised Patients - Mahmoud Shehab Al-heety1 , Sarab Fawzi Al-Ani2, Maher Ali Jasem3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The common opportunistic parasites which cause morbidity and/or death in immunocompromisedpopulations are predominantly gastrointestinal ones. This study explained the molecular and parasitologicalaspects on selected opportunistic intestinal parasites in selected groups of immune compromised patientsfrom Al-Anbar hospitals and private laboratories.In the current study, were taken (130) stool samples from immune compromised patients divided into threegroups (50) chemotherapy recipient, (40) chronic renal failures, (40) diabetic Mellitus, and (30) samplesapparently healthy as control. A questionnaire was filled out on each subject including all personal andmedical history. Stool samples were collected from all groups for detection of the parasites.The results were displayed the ratio of opportunistic parasites in (55.3)% of patients, and healthy controlwas (3.3)%. The results showed that the highest group had parasites in those with chemotherapy (64)%,chronic renal failure (57.5)%, and diabetic (42.5)% individually. The highest rate of infection appeared withBlastocystis hominins(26.1%), Cryptosporidium(22.3%), and Cyclospora cayetanensis (8.4%). The age ofthe patient was ranged between 4-66 years, the Mean was 47.5 and deviation was± 9.12, also, the weightof the patient was ranging between 14-85, the mean was 70.3 and deviation ± 8.07. Three cases of mixedinfection were detected.